2021
DOI: 10.3390/nu13061898
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Serum Copper Status to Survival in COVID-19

Abstract: The trace element copper (Cu) is part of our nutrition and essentially needed for several cuproenzymes that control redox status and support the immune system. In blood, the ferroxidase ceruloplasmin (CP) accounts for the majority of circulating Cu and serves as transport protein. Both Cu and CP behave as positive, whereas serum selenium (Se) and its transporter selenoprotein P (SELENOP) behave as negative acute phase reactants. In view that coronavirus disease (COVID-19) causes systemic inflammation, we hypot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 72 publications
1
62
1
5
Order By: Relevance
“…However, in our study, the difference in serum copper levels in relation to severely ill patients is very small when compared to mild and moderate groups. Contrary to our results, a study in Germany did not find any relative change in serum copper levels during the hospital stay [ 38 ]. The recent study also found a weak and non-significant positive correlation with both PCT and hsCRP which is in agreement with the results of the study done by Fooladi et al [ 37 ].…”
Section: Discussioncontrasting
confidence: 99%
“…However, in our study, the difference in serum copper levels in relation to severely ill patients is very small when compared to mild and moderate groups. Contrary to our results, a study in Germany did not find any relative change in serum copper levels during the hospital stay [ 38 ]. The recent study also found a weak and non-significant positive correlation with both PCT and hsCRP which is in agreement with the results of the study done by Fooladi et al [ 37 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Analysis of a cross-sectional study [20] in Germany of 35 COVID-19 patients (171 serum samples) showed that circulating selenium and SELENOP concentrations increased in the discharge group (n = 29) during hospitalization and unlike deaths (n = 6), and generally the amount of selenium and SELENOP in serum was higher in discharged patients compared to deaths. These authors also investigated the circulating level of selenium and SELENOP in 35 patients (173 serum samples, discharges = 28, deaths = 7) in another study, and the results go along with each other [27]. Another study [22] conducted by the same research team on 33 COVID-19 patients suggested remarkably lower levels of serum selenium, SELENOP, and glutathione peroxidase-3 in deaths comparing to discharges.…”
Section: Serum Selenium Level and Mortality Of Covid-19mentioning
confidence: 81%
“…People with metal deficiency are susceptible to COVID-19 [ 16 , 18 , 19 , 23 , 72 ], which may be due to being out of balance in immune regulation. Supplementing metal nutrients in the early stages of infection can help support optimal immune function and be used as a preventive strategy for high-risk groups [ 73 ].…”
Section: Metal-related Prevention and Treatment Strategiesmentioning
confidence: 99%
“…Some metal elements, such as selenium, iron, and copper, are known to interrupt the infectious interaction between the virus and the host, preventing the virus from entering the host and/or alleviating the symptoms [ 15 18 ]. Trace metal elements such as zinc, selenium, and magnesium are known to play an important role in regulating the human immune system, and their deficiencies are related to the severity of the symptoms in COVID-19 patients [ 19 25 ].…”
Section: Introductionmentioning
confidence: 99%